(3MjGI GdCQhGM hGdOdjd Edi WQjb GdUdGM hGdadGMs - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdPi dG jSJaJM dg hLhO aEfg deG cGf cJGHi gPG LeYJg ef cdGe QH GdYGdejf , hef Sff SjO GdeQSdjf , ef C;hGd GdUGdMjf , de jSHb Edi eKdg ef GdeJbOejf s
(3BNQgG (B:s
(3hGYde Cf gPg GdCdaGX jhge XGgQgG hEfeG jba Ydi eYGfjgG hfYhP HGddg ef Jdc GdYbhHI hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B6s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B424s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(710) s
Keywords: (3Gdabg GdESdGejs